Pengupahan Penggilingan Padi dalam Kajian Fiqh Muamalah - Ahmatnijar, Baharuddin Soleh Daulay Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The implementation of wages for rice mills in Hasahat Jae Village has experienced continuous unrest in the community, there is no transparency and detailed explanation regarding the collection of wages. Therefore, the purpose of this study is to find out how the wage implementation of rice mills and how the muamalah fiqh review of the implementation of rice milling wages that occur in Hasahatan Jae Village. This type of research is field research using qualitative descriptive analysis method. The results showed that there are 3 types of rice milling service wages, namely the implementation of rice milling wages paid with rice, the implementation of rice milling wages paid in money and the implementation of rice milling wages using transportation. In practice, the rice wage is only known unilaterally, namely the mill. Money wages are only made by the Toke and people who earn a lot in the transaction are also not fulfilled the principle of justice. The wage for milling rice uses transportation. The wages are taken from the leftover milling bran. The implementation of the wage for rice milling that occurs in Hasahat jae Village is not fully in accordance with the Muamalah Fiqh study.